2011
DOI: 10.1007/s10875-011-9600-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment with Infliximab for Inflammatory Colitis in a Patient with X-linked Anhidrotic Ectodermal Dysplasia with Immunodeficiency

Abstract: X-linked anhidrotic ectodermal dysplasia with immunodeficiency (X-EDA-ID) is caused by hypomorphic mutations in the gene encoding nuclear factor-κB essential modulator protein (NEMO). Patients are susceptibile to diverse pathogens due to insufficient cytokine and frequently show severe chronic colitis. An 11-year-old boy with X-EDA-ID was hospitalized with autoimmune symptoms and severe chronic colitis which had been refractory to immunosuppressive drugs. Since tumor necrosis factor (TNF) α is responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…Because the dominance of the memory phenotype and the skewed TCR repertoire among CD8 ϩ T cells in NEMO normal cells were observed in both patients 1 and 2 ( Figure 1C and Mizukami et al 18 ), continuous infection of pyogenic bacteria in patient 1 and M szulgai in patient 2 could be a reason for the emergence of NEMO normal cells and the elimination of NEMO low cells. The decrease in NEMO normal cells and restoration of NEMO low cells after anti-mycobacterial therapy in patient 2 support this hypothesis.…”
Section: Org Frommentioning
confidence: 81%
See 4 more Smart Citations
“…Because the dominance of the memory phenotype and the skewed TCR repertoire among CD8 ϩ T cells in NEMO normal cells were observed in both patients 1 and 2 ( Figure 1C and Mizukami et al 18 ), continuous infection of pyogenic bacteria in patient 1 and M szulgai in patient 2 could be a reason for the emergence of NEMO normal cells and the elimination of NEMO low cells. The decrease in NEMO normal cells and restoration of NEMO low cells after anti-mycobacterial therapy in patient 2 support this hypothesis.…”
Section: Org Frommentioning
confidence: 81%
“…The decrease in NEMO normal cells and restoration of NEMO low cells after anti-mycobacterial therapy in patient 2 support this hypothesis. In the case of patient 1, the predominance of NEMO normal T cells with an effector/memory phenotype at diagnosis (Table 4 and Mizukami et al 18 ) is likely to be the result of chronic infection, and it is possible that NEMO low cells were predominant during his early infancy. Because some reports have indicated that TNF-␣-induced programmed cell death of several cell types, including a human T-cell line, was enhanced by hypomorphic NEMO mutations, 12,35 and considering our finding that the levels of TNF-␣ expressed in revertant T cells were similar to levels in healthy control T cells in vitro ( Figure 1F), TNF-␣ produced from these cells in response to infection could be involved in mutant T-cell elimination.…”
Section: Org Frommentioning
confidence: 94%
See 3 more Smart Citations